Beyond the “Revolving Door?”: Incentives and Criminal Recidivism in a Mental Health Court - Snedker, Karen A. (Criminal justice and behavior, 2017)
Specialized mental health courts (MHCs) address the growing problem of defendants with mental illness cycling through the criminal justice system. Employing a mixed-methods approach, this article explores if MHCs can slow the “revolving door” of criminal justice involvement. We use quantitative data to evaluate the effectiveness of one MHC on different measures of criminal recidivism with logistic regression, event history analysis, and negative binomial regression. Modeling strategies report that graduates of MHC, defendants offered a dismissal of criminal charges, and defendants who maintained the same noncrisis mental health treatment while in court as they had prior to court had lower odds of new criminal charges, a longer time to a new criminal charge, and fewer new criminal charges. Qualitative data—court observations and interviews—suggest that providing incentives for program compliance, connecting defendants to planned mental health treatment services, and court completion are central to reducing recidivism.